Pemanfaatan Potensi Lokal Buah Pisang Dalam Upaya Pengentasan Kemiskinan di Desa Tambakrejo, Kecamatan Tambakrejo - Safitri, Risa Anggi; Suwatiningsih, Dewi; Setyaningrum, Dyah (Abdimas Universal, 2025)
Indonesia is an agricultural country with a variety of natural products that are very abundant, one of which is banana fruit. One of the areas with banana producers in East Java province such as Tambakrejo village, Tambakrejo sub-district, Bojonegoro Regency. The KKNTK-14 team of Bojonegoro University held product innovation training in the form of chocolate banana chips to increase the value of bananas. This activity is based on the fact that many bananas are sold only in the form of fruit directly in the market so that unsold fruit will rot and lose. This women's empowerment activity through training aims to increase the selling value of bananas which will encourage increased sales and can help increase the income of sellers or business actors. This activity was carried out on August 05, 2024 with the location of the activity at Tambakrejo Village Hall. The targets of this women's empowerment program are PKK mothers and MSME players in Tambakrejo Village. The implementation of women's empowerment activities goes through several stages such as the preparation stage, the material preparation stage and the activity implementation stage. Based on the implementation of these activities, it can be said that the participants were very enthusiastic in practicing what had been conveyed by the implementer regarding the processing of melted chocolate banana chips at each stage. This activity provides benefits for women in Tambakrejo Village to maximize the existing local potential and improve skills that will later be able to help them improve their livelihood.